Healthcare Access: A Hybrid Systematic Literature Review and Bibliometric Analisis - Wa Ode Fifin Annur; Ismiliani Saflia; Habriani Habriani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Healthcare Access has been a central focus of research over the past few decades; nevertheless, in-depth investigations of this topic remain limited. This study conducts a Systematic Literature Review (SLR) and a bibliometric analysis of Healthcare Access using articles indexed in the Scopus database from 1990 to 2025, yielding 91,938 publications. The SLR evaluation was carried out on July 30, 2025. Bibliometric analysis with VOSviewer was employed to uncover emerging trends and patterns in the literature. The results indicate that Healthcare Access attracts attention not only in countries with advanced health systems but also in developing countries that face challenges in providing equitable and affordable services. Future research should broaden its scope to countries with developing health systems, such as those in Southeast Asia and Africa. In addition, community participation emerged as a critical factor, with six core attributes: affordability, availability, geographic accessibility, information quality, awareness, and community participation. The study also identifies the need for infrastructure development and deeper community engagement to achieve fair and equitable health outcomes.